PENGEMBANGAN MEDIA PEMBELAJARAN IPA DENGAN MENGGUNAKAN OBJEK WISATA DAN PANTAI - Syifa Aulia; Shania Salsabila; Dede Indra Setiabudi (Pusat Riset dan Inovasi Nasional, 2022)
Pancer Door Beach is a place that is very popular with all people, from parents to children. In addition to existing tourist attractions, a large area, and several places to exercise, as well as a very busy buying and selling the place and a place for learning for students to be part of the concepts in learning. The advantage of the Pancer Door beach tourism object is its large waves. For visitors who want to enjoy culinary tourism in the Pancer Door beach area, they also provide stalls around the beach area and many other supporting facilities. Tourist objects can be used for students to learn in open spaces. Like fishers looking for fish, students can immediately see how the fishers catch fish and what types of marine life are caught—then planting mangrove plants around the coast, which can prevent beach abrasion. The application of learning using the Pancer Door beach tourism object as one of the learning aids that can improve student learning outcomes in science learning, teachers must take advantage of the environment to improve student learning outcomes. The proximity of students to learning resources that come from the environment to culture is interesting.